Environmental regulation and renewable energies: Evidence from generalized panel unconditional quantile regression - Amal Rahmane; Okba Abdelaoui; Issam Djouadi (Central European Economic Journal (CEEJ), 2024)
This study aims to measure the impact of environmental regulation on the production of renewable energies in OECD countries from 1990 to 2021. Environmental policies stringency, environmental taxes, and CO2 emissions are variables indicating environmental regulation, which affect renewable energies production. The study relied on unconditional quantitative regression methods. The study found that strict environmental policies do not necessarily enhance renewable energy production in countries with high or low production. Moreover, environmental tax revenues have varying impacts on renewable energy production based on renewable energy production in each country. For countries with below-average levels of renewable energy (Q25), environmental taxes positively affect renewable energy production; however, in countries with high production levels (Q90), environmental taxes show a negative effect. Furthermore, CO2 emissions negatively affect the total production of renewable energy in all quantiles except Q50, whereas R&D spending positively affects renewable energies in all quantiles except Q75. The estimates also showed a significant negative effect of patents on the renewable energy production in quantile Q10. The results underscore the importance of flexibility and adaptability in environmental policies and taxes. Finally, the study indicates that policies must be dynamic and respond to the specificity of each stage of renewable energy development in the studied countries.
Keywords: C01; K32; Q42; 330; stringency of environmental policies; environmental taxes; CO2 emissions; production of renewable energies; quantile regression